Verbal and No-verbal reinforcement approacher is emotion control to increase self-confidence of elementary school students - Veni Veronica Siregar; Nurhasnawati; Siti Fatonah (Universitas Pendidikan Ganesha, 2022)
There are still many teachers who sometimes don't realize that emotional intelligence and self-confidence have a related unity where if someone has been able to control himself and have emotional intelligence, students will be able to place themselves in all situations. Verbal and non-verbal approaches are used to be able to motivate someone such as praise, and applause. This study aims to analyze how verbal and non-verbal approaches are in controlling emotions so that they can make students have individual self-confidence. In this study, this research method used a qualitative descriptive method with data collection, namely observation, interviews, documentation and directly involved in finding the necessary information. The subjects of this study were elementary school students. The data analysis technique used by the authors in this study is through four sub-processes, namely data collection, data reduction, data display and data verification. The results that the researchers got were that with verbal and non-verbal approaches they could control students' emotions and have self-confidence, such as self-responsibility, self-confidence, and ability to accept criticism and suggestions from others.